Membandingkan Cetakan Terbuka Dengan Tertutup Pada Pembuatan Papan Skate Board Dari Limbah Sawit - M Yani; Bekti Suroso (Rekayasa Material, Manufaktur dan Energi, 2019)
This study aims to compare open and closed molds, hand lay-up method in the manufacture of skate board boards from oil palm empty fruit bunches (OPEFB) fiber reinforced composites. The constituent materials of this composite are OPEFB fiber and unsaturated polyester resin. The mixing of both of materials with the ratio of the composition of the OPEFB fiber and polyester resin is made based on a volume fraction of 20:80. The diameter of the OPEFB fiber that is used ranges from 0.1 to 0.8 mm mixed into the unsaturated polyster resin liquid. OPEFB fibers are arranged longitudinally with one layer according to the thickness of the skate board. Skate board prints made using a cover have smooth surfaces on both sides. However, to ensure that the resin has filled the entire surface of the mold from a closed mold seen from the presence of resin that comes out of the closing gap. This resin can not be used anymore because it will dry up and freeze. When compared with printouts without pentup has a rough surface on the top side of the skate board. The conclusion is that the use of closed molds has better results when compared to open molds.